SIKAP KONSUMEN DAN STRATEGI PEMASARAN DUA MEREK KOPI BUBUK DI KOTA BANDAR LAMPUNG - Epriani, Mera; Endaryanto, Teguh; Indriani, Yaktiworo (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims to determine the consumer’s attitude, marketing strategy, and marketing performance of two branded coffee powder in Bandar Lampung. Two coffee brands were chosen purposively, namely SBCBD and 49 for it’s famous and unfamous the community. The samples of coffee consumer’s were 70 people were chosen by accidental sampling, while samples of the marketing strategy were chosen by purposive adjusted by the location of this research. The research data was analyzed by descriptive qualitative, descriptive quantitative, and multi-attribute Fishbein model. The results showed that coffee consumer’s was dominated by aged 15-64 years old with the occupation as a housewife that graduated from high school, and have 3-5 family members, purchased coffee powder less than 6 times per month with incomes more than Rp2,500,000.00 per month. However base on the packaging size of the coffee powder, the consumer’s of Coffee Powder SBCBD like the packaging size more than >200 grams, but the consumer’s of Coffee Powder 49 like the packaging size of 200 grams. The result of the analysis on attitude of consumer’s, the taste of coffee powder got the highest score on the analysis of consumer’s attitude. The marketing strategy has been implementing the aspects of the marketing mix (product, price, place, and promotion). The marketing performance of Coffee Powder 49 was better applied than Coffee Powder SBCBD. Key words: attitudes, coffee powder, marketing, taste